Implementation of Regional Regulation Policy on Waste Management in Malang Regency - Tri Setyoprambudi; Bonaventura Ngarawula; Sri Hartini Jatmikowati (LPPM Institut Teknologi dan Sains Mandala, 2025)
This study aims to analyze the implementation of the regional regulation policy on Edu Sampah Cipta Kerja, as well as to identify the supporting and inhibiting factors. The research location was the Reduce-Reuse-Recycle Integrated Waste Management Site (TPST 3R) in Mulyoagung Village, Dau District, Malang Regency. The data analysis technique uses a qualitative method that collects, reduces, presents data, and draws conclusions interactively and continuously. The results showed that implementing the Edu Sampah Cipta Kerja program in Mulyoagung Village increased community understanding and participation in community-based waste management. Effective communication and policy transparency strengthened community involvement despite initial resistance. The bureaucratic structure in the TPST 3R managed by the Community Self-Help Group (KSM) is running well but requires operational consistency. Dispositional factors reflect the high commitment of relevant institutions, but policy sustainability still depends on financial and labor management. The main supporting factor is the synergy between the government and the community, while the biggest challenge is the limited operational workforce. Continued support and improvement of human resources are key to the sustainability of waste management in Mulyoagung Village. It is expected that the results of this study contribute to improving the effectiveness of the Edu Sampah Cipta Kerja program through continuous socialization, financial transparency, evaluation of the payroll system, and participatory monitoring for the sustainability of waste management in Mulyoagung Village.